Intraocular Chondrosarcoma in a Rabbit. (August 2020) - Mikiewicz, M.; Paździor-Czapula, K.; Gesek, M.; Dziubińska-Bartylak, P.; Otrocka-Domagała, I.
Summary: Post-traumatic intraocular sarcomas are rarely reported in domestic animals and are most common in cats. An 8-year-old rabbit ( Oryctolagus cuniculus ) was referred to a veterinary clinic due to ocular discharge, uveitis and protein precipitate in the anterior chamber of the right eye. The eye was enucleated and histopathological examination revealed a poorly demarcated tumour within the ciliary body with invasion to adjacent eye structures. Neoplastic cells formed chaotic cartilage lacunae and were immunopositive for vimentin but immunonegative for pancytokeratin. On this basis, the neoplasm was diagnosed as a chondrosarcoma. To the best of our knowledge, this is the first report of intraocular chondrosarcoma in a rabbit. There was no history of previous ocular trauma but as there was serological evidence of Encephalitozoon cuniculi infection, inflammation could have been a predisposing factor to development of the neoplasm.